THE INFLUENCE OF BRAND EQUITY AND BRAND TRUST ON PURCHASING DECISIONS THROUGH COMPETITIVE ADVANTAGE OF EXOTIC BRAND CORN SEED PRODUCTS AT DUTA TANI STORE - Gede Yuda Mahendra; Ni Putu Widhia Rahayu (Universitas Nusa Cendana, 2026)
This study aims to examine the influence of brand equity and brand trust on purchasing decisions with competitive advantage as a mediating variable for Exsotic brand sweet corn seed products at Duta Tani Store. The study is motivated by fluctuations in product sales over the past three years and the increasing competition in the agribusiness sector. This research uses a quantitative approach with an explanatory research design. The population consists of consumers who have purchased Exsotic brand sweet corn seeds at Duta Tani Store, with the sample selected using purposive sampling involving 60 respondents. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The results show that brand equity does not significantly influence competitive advantage or purchasing decisions. In contrast, brand trust has a positive influence on competitive advantage. Furthermore, competitive advantage plays a role as a mediating variable in influencing purchasing decisions. Overall, the research model demonstrates strong predictive capability. These findings suggest that strengthening brand trust is an important strategy for Duta Tani Store in building competitive advantage and encouraging consumer purchasing decisions. Keywords: Brand Equity; Brand Trust; Competitive Advantage; Purchasing Decisions